2012
DOI: 10.1111/j.1349-7006.2012.02309.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of DNA polymerase iota (Polι) in esophageal squamous cell carcinoma

Abstract: The present study investigated the transcriptional regulation of low-fidelity translesion DNA synthesis (TLS) polymerases in human esophageal carcinoma. Significantly higher mRNA expression of polymerase zeta (Polξ), RAD18, polymerase iota (Polι), and polymerase kappa (Polj) was found in esophageal carcinomas. The increased expression of Polι in tumor samples was further confirmed by immunohistochemistry. The promoter of POLI that encodes Polι was found to be hypomethylated, although the overexpression of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 29 publications
(28 reference statements)
2
27
0
Order By: Relevance
“…Genomic DNA was extracted from cells using the SDS and proteinase K methods and then subjected to sodium bisulfite treatment as reported previously 21,22. The converted DNA was subjected to analysis via the Illumina Infinium Human Methylation 450K BeadChip by Genergy Biotech (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was extracted from cells using the SDS and proteinase K methods and then subjected to sodium bisulfite treatment as reported previously 21,22. The converted DNA was subjected to analysis via the Illumina Infinium Human Methylation 450K BeadChip by Genergy Biotech (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…For instance Malkas' group identified an elevated expression of Pol ι in human breast cancer cells, which was correlated with decreased DNA replication fidelity [20]. We have recently demonstrated that the expression of Pol ι is upregulated in ESCC tissues [21, 22] and that the dysregulation of Pol ι harasses cell cycle progression through enhancing cyclin D1 expression [22]. However, the relationship between Pol ι expression and tumor invasion and metastasis of ESCC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Determining how these bacterial enzymes are regulated will allow a better description of the regulation of TLS polymerase activity in other systems. Furthermore, TLS polymerases have been implicated in the evolution of antibiotic resistance in bacteria and cancer in humans (24)(25)(26)(27). Deregulation of TLS polymerases, therefore, has a variety of deleterious consequences in both prokaryotic and eukaryotic organisms.…”
mentioning
confidence: 99%